1987
DOI: 10.1111/j.1532-950x.1987.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Drainage Procedures: Effects in Normal Dogs II. Clinical Observations and Gastric Emptying

Abstract: Complete gastric emptying time using barium sulfate mixed with commercial canned dog food was measured radiographically in 29 mature mixed breed dogs before and 3 to 4 weeks after Fredet-Ramstedt pyloromyotomy (FRP) (6 dogs), Heineke-Mikulicz pyloroplasty (HMP) (6 dogs), Finney pyloroplasty (FP) (6 dogs), Jaboulay's gastroduodenostomy (JG) (6 dogs), and antral gastrojejunostomy (AG) (5 dogs). The dogs were observed for clinical evidence of side effects. Postoperative endoscopic examination and double contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…No difference among the different conventional surgical techniques could be demonstrated. 14,17 In our study, the total gastric emptying time varied between 5 and 11 h in the preoperative period. Other studies have reported a complete gastric emptying time of around 5-15 h in normal dogs and a great individual variability in these results.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…No difference among the different conventional surgical techniques could be demonstrated. 14,17 In our study, the total gastric emptying time varied between 5 and 11 h in the preoperative period. Other studies have reported a complete gastric emptying time of around 5-15 h in normal dogs and a great individual variability in these results.…”
Section: Discussionmentioning
confidence: 73%
“…16 A limitation of the current study involves the incapacity to determine the rate of gastric emptying. 17 Although pyloroplasty is frequently used in dogs, previous studies 14,17,19,20,41 have shown faster emptying of liquids and no change in the emptying of solids following pyloroplasty. Other studies 5,33,42,43 have shown that Heineke-Mikulicz pyloroplasty is associated with an enhanced postoperative gastric emptying, even compared with Ramstedt pyloromyotomy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations